Unraveling the Complexities of Severe Dengue: Exploring Transfusion Avoidance Strategies with Management of Hematological, Radiological Parameters, Clinical Features : Blood transfusion avoidance Strategies in severe dengue patients - Singh, Ranbeer; Singh, Chhaviraj; Singh, Swati; Singh, Puja (Universitas Brawijaya, 2024)
Background: Dengue is an entity caused by mosquito bites in humans. It can change into a life-threatening entity within a very short time. Not every dengue case requires a blood transfusion. While plasma leakage and a drop in platelet count are possible side effects of severe dengue, not all patients suffer from them. The main goals of treatment are to control symptoms such as pain, fever, and dehydration by giving patients enough fluids and medicine. Aim: To identify the various clinical features associated with dengue along with the manifestations not warranting blood transfusion. Methods: This observational study includes a total of 300 laboratory-verified dengue patients who were admitted over two months. Patients with other causes of fever were excluded. Results: The majority of patients (80%) were discovered to be between the ages of 10 and 40, indicating that people in this age bracket are often more afflicted. Males were predominantly affected in comparison to females. Thrombocytopenia is the most prevalent anomaly, present in all the patients. Of these, 3.0 (1.0%) had platelet counts < 10,000/cmm, while 198 (66%) had platelet levels < 10,000–20,000/cmm. Conclusion: We conclude that the main factors influencing the prognosis are intra-abdominal visceral oedema as gall bladder wall edema, leucopenia (TLC count below 2000 cells/cmm), deranged liver functions, capillary leakage leading to peritoneal/pleural effusions as well as shock, and platelets. Platelets do not determine the severity and fatality of dengue infection.